Student’s Perception on the Implementation of “English with Emma” YouTube videos as a Vocabulary Building Strategy at SMKN 1 Padang - Afif, Ahmad Fajar; Rani, Yati Aisya (Journal of English Language Teaching, 2024)
This study aim to figure out How is the Students' Perception on the Implementation of "English with Emma" YouTube Videos as a Vocabulary Building Strategy at SMKN 1 Padang. This research used a descriptive method. The participants in this study were 32 students of X1.1 class at SMKN 1 Padang who have watched "English with Emma" YouTube Videos. The data were collected using close-ended questionnaires. According to the findings, it can be concluded that the perception of most students on the implementation of English with Emma YouTube Videos as a Vocabulary Building Strategy is very positive. It means that Emma’s YouTube videos is very useful to reinforce vocabulary enrichment for most of the students.